Black mass [videorecording (Blu-Ray + DVD)] - Mallouk, Mark, 1973-; Butterworth, Jez; Depp, Johnny; Edgerton, Joel, 1974-; Cumberbatch, Benedict, 1976-; Johnson, Dakota, 1989-; Cochrane, Rory; Plemons, Jesse, 1988-; Bacon, Kevin, 1958-; Sarsgaard, Peter; Junkie XL, 1967-; Maimone, Kasia Walicka; et al. (Warner Bros. Entertainment, Inc., 2016)
In 1970s South Boston, FBI agent John Connolly persuades Irish mobster Jimmy Bulger to collaborate with the FBI in order to eliminate their common enemy: the Italian mob. The drama tells the story of this unholy alliance, which spiraled out of control, allowing Whitey to evade law enforcement while consolidating his power and becoming one of the most ruthless and dangerous gangsters in Boston history.